2007
DOI: 10.1055/s-2007-959157
|View full text |Cite
|
Sign up to set email alerts
|

Unbehandelte Posttraumatische Belastungsstörungen bei schizophrenen Störungen: eine Hypothek auf die Zukunft?

Abstract: More recently research has focused on post-traumatic stress disorder (PTSD) as comorbide condition of schizophrenia. Current literature focussing the relationship between PTSD and schizophrenia is reviewed. Evidence is found in support of psychosis as a precondition for development of PTSD, PTSD as vulnerability factor for psychosis as well as psychosis and PTSD both as part of a spectrum of responses to a traumatic event. PTSD may be regarded as risk factor for worse outcome in schizophrenia: Internal stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
1
0
3
Order By: Relevance
“…Additionally another study found that the rate of PTSD (4.0%) was larger than that of psychotic disorders (2.9%) in a sexually abused sample (Cutajar et al, 2010b). Despite the complex interrelation between posttraumatic symptoms, psychotic symptoms, and TLEs, there is minimal agreement as to whether psychosis is a risk factor for PTSD, whether PTSD is a risk factor for psychosis, or whether both disorders represent a continuum response to TLEs (Vauth & Nyberg, 2007). One theory is that exposure to childhood trauma may enhance risk for stress-related disorders (e.g., psychosis, PTSD, depression) via the neuropathology of the stress response system (i.e., alterations of the hypothalamic-pituitary-adrenal [HPA] axis; Matheson et al, 2012).…”
Section: Multifinalitymentioning
confidence: 99%
“…Additionally another study found that the rate of PTSD (4.0%) was larger than that of psychotic disorders (2.9%) in a sexually abused sample (Cutajar et al, 2010b). Despite the complex interrelation between posttraumatic symptoms, psychotic symptoms, and TLEs, there is minimal agreement as to whether psychosis is a risk factor for PTSD, whether PTSD is a risk factor for psychosis, or whether both disorders represent a continuum response to TLEs (Vauth & Nyberg, 2007). One theory is that exposure to childhood trauma may enhance risk for stress-related disorders (e.g., psychosis, PTSD, depression) via the neuropathology of the stress response system (i.e., alterations of the hypothalamic-pituitary-adrenal [HPA] axis; Matheson et al, 2012).…”
Section: Multifinalitymentioning
confidence: 99%
“…matischer Syndrome berichtet. So weisen 29 -39 % der Patienten mit Schizophrenie, schizoaffektiven und bipolaren Störungen eine komorbide PTBS auf [9]. Auch dissoziative Symptome, die signifikante Zusammenhänge mit frühen Traumatisierungen zeigten, komorbide dissoziative Störungen und "Mischbilder" wurden bei Patienten mit psychotischen Störungen wiederholt beschrieben [10].…”
Section: Abstract !unclassified
“…Psychotische wie dissoziative Symptome müssen in der Regel explizit erfragt werden, ansonsten erfährt man darüber nichts [17]. Da psychotische und dissoziative Symptome nicht zu allen Zeiten explorierbar sind oder es mitunter auch schwierig ist, zwischen dissoziativen und psychotischen Qualitäten zu unterscheiden [9,15], muss wiederholt danach gefragt werden. Bei sehr komplexen Fällen sollte sowohl die PTBS-, die dissoziative als auch die psychotische Symptomatik idealerweise anhand strukturierter Instrumente (etwa SKID-I und SKID-D) diagnostiziert werden.…”
Section: Diagnostische Und Behandlungstechnische Konsequenzenunclassified
“…In allgemeinpsychiatrischen Einrichtungen liegen die Komorbiditätsraten sogar über 50% (Vauth & Nyberg, 2007). In der vorliegenden Untersuchung handelt es sich jedoch infolge der hohen komorbiden Suchtbelastung um eine spezielle…”
unclassified